2015
DOI: 10.1111/geb.12363
|View full text |Cite
|
Sign up to set email alerts
|

Using ecophysiological traits to predict climatic and activity niches: lethal temperature and water loss inMediterranean ants

Abstract: Aim Unravelling the constraints acting on the distribution and abundance of species is a major goal in ecology. Climatic niche models have become an important but controversial tool for predicting the consequences of global warming for species distributions. However, to date, classical ecophysiological traits such as thermal tolerance and water loss have rarely been accounted for in species distribution models. Here we meet the challenge of linking ecophysiological measures with climatic niche descriptions at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…Furthermore, the fundamental thermal niches of species are shaped by species-specific physiological constraints; fundamental thermal niches only become realized thermal niches as a consequence of biotic interactions (e.g., competition) and demographic/dispersal constraints (see Meier et al, 2010 for an example). Interestingly, a previous study utilizing the subset of ant species examined here demonstrated that species physiological thermal tolerance and biogeographic climatic niches (i.e., realized climatic niches) were strongly correlated (Arnan and Blüthgen, 2015). Third, estimations of species thermal niche indices based on species records are obviously scale dependent; our species-specific thermal niche indices may therefore be biased.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, the fundamental thermal niches of species are shaped by species-specific physiological constraints; fundamental thermal niches only become realized thermal niches as a consequence of biotic interactions (e.g., competition) and demographic/dispersal constraints (see Meier et al, 2010 for an example). Interestingly, a previous study utilizing the subset of ant species examined here demonstrated that species physiological thermal tolerance and biogeographic climatic niches (i.e., realized climatic niches) were strongly correlated (Arnan and Blüthgen, 2015). Third, estimations of species thermal niche indices based on species records are obviously scale dependent; our species-specific thermal niche indices may therefore be biased.…”
Section: Discussionmentioning
confidence: 78%
“…It was assumed that the niches were well described by the mean and standard deviation of the thermal conditions in which the species occur. Species thermal niches often follow a Gaussian distribution (Huey and Kingsolver, 1993), which was also true of the niches of the subset of ant species used in this study (Arnan and Blüthgen, 2015). We calculated the following two species-level indices, which are illustrated in Figure 1A.…”
Section: Thermal Nichesmentioning
confidence: 99%
See 1 more Smart Citation
“…A third explanation for the ecological packing is that the morphological traits used here are weakly related to Pheidole ecological niches and, therefore, functional packing is unlikely. This alternative is however questionable given the strong evidence linking ant morphological traits with physiological (Arnan & Blüthgen, ; Arnan et al, ; Bishop et al, ), behavioral (Hurlbert, Ballantyne, & Powell, ; Medan & Josens, ), and life‐history traits (Weiser & Kaspari, ). Most likely, the similarities in morphological traits among Pheidole species do reflect similar ecological adaptations, which ultimately indicate that increased niche packing rather than niche displacement underlies the diversity pattern of Pheidole assemblages in Neotropical savannas.…”
Section: Discussionmentioning
confidence: 99%
“…Ant preferences for EFN-bearing plants depend on EFN nectar amount and composition Fiedler 2004a, b, Bixenman et al 2011), and nectar production is highly dependent on abiotic and biotic factors (Bixenman et al 2011, Alves-Silva andDel-Claro 2014). In addition, the physical conditions of microhabitats determine the spatial and temporal foraging patterns of ants (Fitzpatrick et al 2014, Arnan andBlüthgen 2015). Thus, in more environmentally unstable areas (probably the most disturbed and arid areas), shifts in ant foraging patterns and plant preferences may be more pronounced from year to year, thus increasing temporal instability in interaction networks.…”
Section: Introductionmentioning
confidence: 99%